(untitled) (Ustozlar uchun, 2024)
The Republic of Uzbekistan has been developing its debt policysince its independence in 1991. This policy is crucial for maintaining thecountry's economic stability and fostering sustainable development. This articleexamines the legal frameworks and institutional arrangements that underpinUzbekistan's debt policy. It provides an analysis of the legislation governingpublic debt, the roles of various government bodies, and the mechanisms fordebt management. Furthermore, the article explores the challenges andopportunities faced by Uzbekistan in managing its public debt and suggestspotential improvements to the existing legal structures.